2014
DOI: 10.4049/jimmunol.1302269
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of Alveolar and Interstitial Lung Macrophages in Rhesus Macaques: Implications for Understanding Lung Disease in Humans

Abstract: Alveolar macrophages (AM) obtained by bronchoalveolar lavage (BAL) are commonly used to study lung macrophage-mediated immune responses. Questions remain, however, about whether AM fully represent macrophage function in the lung. This study was performed to determine the contribution of interstitial macrophages (IM) of lung tissue to pulmonary immunity and that are not present in BAL sampling. In vivo BrdU injection was performed to evaluate the kinetics and monocyte/tissue macrophage turnover in Indian rhesus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
167
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(195 citation statements)
references
References 39 publications
(48 reference statements)
24
167
1
Order By: Relevance
“…Cai et al compared blood monocytes and interstitial macrophages in the lungs of rhesus macaques and showed that they express very similar markers, except that interstitial macrophages, unlike monocytes, did not express CCR2, which is important in the recruitment of monocytes from bone marrow to circulation and then to tissues (55,57). However, we were unable to show a downregulation of CCR2 on the monocytes that we identified in BAL.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Cai et al compared blood monocytes and interstitial macrophages in the lungs of rhesus macaques and showed that they express very similar markers, except that interstitial macrophages, unlike monocytes, did not express CCR2, which is important in the recruitment of monocytes from bone marrow to circulation and then to tissues (55,57). However, we were unable to show a downregulation of CCR2 on the monocytes that we identified in BAL.…”
Section: Discussioncontrasting
confidence: 47%
“…The monocytes referred to in our study could also include monocytederived interstitial macrophages as described by others (27,55,56). Cai et al compared blood monocytes and interstitial macrophages in the lungs of rhesus macaques and showed that they express very similar markers, except that interstitial macrophages, unlike monocytes, did not express CCR2, which is important in the recruitment of monocytes from bone marrow to circulation and then to tissues (55,57).…”
Section: Discussionmentioning
confidence: 99%
“…The role of interstitial macrophages as developmental intermediates was supported by observations that proliferation or replenishment of lung macrophages in the interstitial compartment often preceded that of the alveolar compartment following injury, depletion or explant culture (Bowden and Adamson, 1972;Bowden et al, 1969;Higashi et al, 1992;Landsman and Jung, 2007;Lichanska and Hume, 2000;Robinson, 1984;Takeya and Takahashi, 1992), and by ultrastructural and immunohistochemical studies suggesting that interstitial macrophages were intermediate in size and molecular phenotype between monocytes and alveolar macrophages (Cai et al, 2014;Ginhoux et al, 2010;Sebring and Lehnert, 1992). These early models suggested two different sources of lung macrophages (fetal yolk sac and adult bone marrow), but as for skin and cardiac macrophages, developmental origin is unimportant in the models because both sources were thought to give rise to interstitial and alveolar macrophages, with interstitial macrophages as obligate progenitors of alveolar macrophages.…”
Section: Introductionmentioning
confidence: 73%
“…Although existing panels could be applied to the examination of pulmonary immune responses, these are currently limited to the examination of lymphocyte phenotypes and would therefore not allow an examination of the mononuclear phagocytes and granulocytes that represent key components of pulmonary immune responses. In recent years, several protocols have been described for the flow cytometric analysis of immune cells, including mononuclear phagocytes and granulocytes, in animal lung tissues and BAL (4)(5)(6). However, no such protocol currently exists for the examination of human BAL or lung tissues.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Animal studies suggest that macrophages play unique functional roles, depending on whether they are alveolar or interstitial (6,(14)(15)(16)(17). Despite advances made in animal models, studies in humans are typically limited to either macrophages obtained from BAL or derived from circulating monocytes in culture as being representative of pulmonary macrophage function (18).…”
Section: Clinical Relevancementioning
confidence: 99%